Financial Safety Net for Emergency Health Services among Urban Ready- Made Garment Workers in Bangladesh - Adhikari, Upal; Rahman, Ashiqur; Hasan Roman, Md Mesba Ul; Mamun, Abdullah Al; Khanam, Fahmida (International Journal of Human and Health Sciences (IJHHS), 2025)
Background: Bangladesh now has the third-largest proportion of the world’s garment market. Between 4,000 and 5,000 garment manufacturers are said to be located in Bangladesh. It provides a steady stream of work to almost 4,000,000 workers, the majority of whom are women. Sadly, this incredible accomplishment has been hampered by industrial accidents and a lack of production safety, both of which present health risks. Objective: To determine the current status of financial safety net for garment workers for their emergency health events. Methods: This cross-sectional, descriptive study was conducted, between January and December of 2023, among 415 garments workers working in four different factories at Dhaka and Narayanganj districts of Bangladesh. Respondents were selected by convenience sampling technique and face-to-face interview was taken for data collection. We used a pretested semi-structured questionnaire. Results: Most of the respondents were in age range of 18 to 25 years and 57% female and 43% male respondents. Most of the respondents use health care services sometimes (69.4%) and some (50.8%) knowledge regarding emergency health care services. Among the respondents the presence of knowledge of financial safety net was agreed by 35.4% and disagreed by 33.7%. The satisfaction for established financial safety net was agreed by 58.6% and disagreed by 1.2% of the respondents. Most of the respondents agreed that they have out of pocket health expenditure and it was mostly below 1000 BDT. About 38% disagreed that they have the capacity of managing financial burden and 34.7% agreed to the issue. 201 of 415 respondents agreed that they have loan and 63.4% respondents disagreed that they perceived financial safety from their garments. Conclusion: Despite having higher knowledge and satisfaction regarding financial safety net improvement is recommended to overcome the loan and increase savings for emergency health services for the garment workers. International Journal of Human and Health Sciences Vol. 09 No. 04 Oct’25 Page: 231-236